Immune responses to SARS-CoV-2 in three children of parents with symptomatic COVID-19 - Shidan Tosif (Nature Portfolio, 2020)
Children with SARS-CoV-2 infection are more likely to have mild symptoms and may be asymptomatic, but underlying reasons remain unclear. Here, the authors show cellular, cytokine and antibody response to SARS-CoV-2 infection in three children who repeatedly tested negative for the virus by PCR, despite high exposure in the household.